The Influence of Student Team Achievement Divisions (STAD) Learning Model Containing Science Literacy on Student’ Learning Competencies at SMAN 1 V Koto Kampung Dalam - Wita Febriani; A. Ardi; Resti Fevria; S. Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2019)
This research is based on the problems that exist in SMAN 1 V Koto Kampung Dalam, which have an impact on the low learning outcomes of students. Efforts that can be made are implement the learning model Student Team Achievement Divisions (STAD) with scientific literacy on respiratory system material at SMAN 1 V Koto Kampung Dalam. The purpose of this study was to determine the increase in the competency of students through the model Student Team Achievement Divisions (STAD) with scientific literacy in the material of human respiratory system in SMAN 1 V Koto Kampung Dalam. This type of research is experimental research with a Randomized control group posttest only design. The population in this study were all class XI IPA SMAN 1 V Koto Kampung Dalam registered in the 2018/2019. Sampling was done using technique Purposive Sampling, which was chosen as the sample of the study was class XI IPA 4 as the experimental and XI IPA 3 as the control class. The instruments used were in the form of questions posttest for knowledge competency, observation sheets for attitude and skills. The hypothesis was tested using the t-test, can be concluded that the competence of learners knowledge tcount 3,80 > ttable 1.67, the competence of attitude  value tcount 3,61 > ttable 1,67, and the competency of skills value tcount 2,00 > ttable 1.67. This shows that the hypothesis is accepted. Concluded that the application of model Student Team Achievement Divisions (STAD) with scientific literacy can improve the competency of knowledge, attitudes, and skills of students class XI IPA of SMAN 1 V Koto Kampung Dalam.